Structural determination of improved methanol-tolerant mutant from Geobacillus zalihae T1 lipase by x-ray crystallography - Medam @ Hamdan, Siti Hajar (2022)
Lipases are versatile enzymes that have been altered through various modification methods to improve their enzymatic properties to meet biotechnology industry requirement. Since decades ago, lipases from many sources have been study widely as potential biocatalyst to assist synthesis of biodiesel. Some of them have been altered via protein engineering approach to enhance their enzymatic performance and stability. The thermostable T1 lipase from Geobacillus zalihae can also be a great biocatalyst candidate in biodiesel production. However, inactivation of T1 lipase when the enzyme is surrounded by high concentration of methanol solvent is limiting its uses in industrial applications. Since introduction of non-bonded interactions hardly improved their stability of T1 lipase in methanol, the introduction of disulphide bond could be the best proposition to retain protein conformation and the enzyme stability in the presence of methanol. Hence, current study aims to engineer a methanoltolerant lipase by site-directed mutagenesis and divulge the interaction that stabilizes the mutant by X-ray crystallography. The preliminary study on enzyme stability was conducted by using online software ERIS, FoldX and MAESTRO. The stability of the mutant 2DC lipase was tested virtually and molecular dynamic simulation was performed in water and methanol solvent. Experimentally, the purified protein of mutant 2DC lipase was used to screen protein crystal for diffraction to elucidate and validate the mutant’s structure. It showed that the substitution of amino acid S2 and A384 with cysteine could enhance the stability of the enzyme by promoting the formation of disulphide bond to tighten the both terminal ends of the protein structure. The substitution of amino acid cysteine showed the changes on the active site distance (S113, D317, and H358), however, it was not affected the lipase activity and folding of protein structure. The 2DC mutant was successfully constructed and cloned into pET32-b and transformed into Origami B (DE3) expression host. The expression and purification using Ni2+-Sepharose affinity chromatography and gel filtration chromatography S-200 of the protein yielding 4.0 mg/ml mutant 2DC lipase suitable for protein crystallization. The mutant 2DC lipase was crystallized after 24-hour incubation at 20°C and diffracted by X-ray crystallography for deeper evaluation in term of stability and rigidity. The crystal was diffracted at 2.04 Å using in-house X-ray beam and the crystal belongs to monoclinic space group C2, with unit cell parameter of a = 118.17, b = 81.5, c = 100.05. Details information on structural elucidation of the mutant 2DC lipase has disclosed the changes within the mutant structure which associated with the alteration of enzyme activity and stability posed by the mutant. The increased in rigidity of the structure as well as changes of interaction within the catalytic region of the mutant 2DC lipase were suggested to be the factor influenced its enzymatic activity, stability and tolerance towards methanol. Hence, this newly improved mutant 2DC lipase could be the next potential biocatalyst in biodiesel production industry.